The Role of Schengen in the Development of Peripheral Borderland Regions - Pásztor, Szabolcs (Acta Agraria Debreceniensis, 2011)
This study aims to uncover the role of the Schengen borders of the European Union in rural and settlement development. Schengen integration applies certain restrictions at the external border-crossings, so the filtering role is to be taken into consideration. In addition to the disappearance of borders in the globalising economic area, the strict Schengen rules further burden the development of cross-border interactions, bringing about less frequent border crossings. Moreover, the economic integration of the affected borderlands would remain sluggish. The author points to the fact that the dynamics of a border interaction system should include a Schengen border degree between the interdependent and integrated borderland levels. Consequently, the Schengen borderlands should be in the focus of further border studies.